2019
DOI: 10.1007/s40520-019-01119-4
|View full text |Cite
|
Sign up to set email alerts
|

Betwixt and between: a surgical post-acute treatment unit (SPA) for the optimal care of elderly patients with isolated hip fractures

Abstract: Background A performance improved project identified elderly trauma patients to have a disproportionate incidence of complications. Aims The purpose of this study was to assess the efficacy of a small specialty care unit to decrease complications in patients who no longer warrant care in an intensive care unit (ICU). Methods A surgical post-acute treatment unit (SPA) was developed with focused attention to cognition, nutrition, respiration, and mobilization needs of patients who no longer had physiologic need … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 89 publications
0
4
0
Order By: Relevance
“…Moreover, this was also shown for perioperative care by multidisciplinary teams [20]. The focused care appears to improve outcomes even in patients requiring intensive care [20,21].…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Moreover, this was also shown for perioperative care by multidisciplinary teams [20]. The focused care appears to improve outcomes even in patients requiring intensive care [20,21].…”
Section: Introductionmentioning
confidence: 82%
“…According to previous studies, the development of Geriatric Trauma Centres showed beneficial effects on outcome after hip fractures [19]. Moreover, this was also shown for perioperative care by multidisciplinary teams [20]. The focused care appears to improve outcomes even in patients requiring intensive care [20,21].…”
Section: Introductionmentioning
confidence: 87%
“…Addressing the care needs of older patients with fallinduced injuries is intricately challenging due to the intertwined comorbidities and diminished physiological reserves associated with aging, complicating both surgical interventions and postoperative recovery [5][6][7][8][9]. In response, various treatment models of orthogeriatric care have been developed in the last decade to better serve the complex healthcare requirements of this demographic [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In response, various treatment models of orthogeriatric care have been developed in the last decade to better serve the complex healthcare requirements of this demographic [10,11]. Comanaged care, where surgical and geriatric expertise converge within specialized units, has been most effective in enhancing patient outcomes [7,8,[11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Although comanaged care has been implemented under various names [5, 7-10, 12, 13, 17, 19-37] worldwide, its fundamental aim remains consistent: optimizing patient outcomes and improving quality of life.…”
Section: Introductionmentioning
confidence: 99%